Does self-modeling affect imagery ability or vividness? - Rymal, A. M.; Ste-Marie, D.-M. (Journal of Imagery Research in Sport and Physical Activity, 2009)
Research has shown imagery interventions to be important tools for learning new skills, as well as enhancing competitive performance. Moreover, imagery vividness and ability are two factors shown to contribute to their effectiveness. Therefore, learning ways to increase one's imagery vividness and ability is important. Hence, the present research examined the effects of an external stimulus (i.e., a self-modeling video) on one's imagery vividness and ability. A self-modeling video is an edited video showing the desired target behaviors; in this case it was a competitive dive. Two imagery measures (VMIQ and MIQ-R) were used to capture whether the self-modeling video would influence competitive divers' imagery vividness and ability. Seven competitive divers were administered both imagery measures at pre-test and post-test. After pre-test scores were taken, the participants' individual self-modeling videos were shown on three occasions before each competition and once at each competition. The results for the VMIQ indicated that imagery vividness when imaging the self was significantly better than when imaging others, F(1,6) = 7.44, p < 0.05, ?2 = .54. Of more importance is that the participants' imagery vividness increased after the self-modeling video had been administered for imaging one self but not for imaging others, although this only approached significance, F(1,6) = 3.70, p = .107, ?2 = .38. No significant results, however, were found for imagery ability. These findings suggest that there is potential for a self-modeling video to positively influence an athletes' imagery vividness.